Income Inequality in France, 1901–1998 - Piketty, Thomas (Journal of Political Economy, 2003)
This paper uses data from income tax returns (191598), wage tax returns (191998), and inheritance tax returns (190294) in order to compute homogeneous, yearly estimates of income, wage, and wealth inequality for twentieth-century France. The main conclusion is that the decline in income inequality that took place during the first half of the century was mostly accidental. In France, and possibly in a number of other countries as well, wage inequality has been extremely stable in the long run, and the secular decline in income inequality is for the most part a capital income phenomenon. Holders of large fortunes were badly hurt by major shocks during the 191445 period, and they were never able to fully recover from these shocks, probably because of the dynamic effects of progressive taxation on capital accumulation and pretax income inequality.